Innovative Accelerated Construction Method for Yushan Bridge. Issue 4 (3rd September 2019) - Chang-jiang, Wang; Lei, Li; Xiang-yang, Chen; Yu-dong, Bai
Abstract : To overcome poor construction conditions, shorten construction time and improve project quality, the construction of Yushan Bridge is fully industrialized based on prefabrication of key components, site installation. The navigation span of the Yushan Bridge has a main span of 260 m and is the world's first segment precast steel-concrete composite continuous beam bridge. A new type of steel-concrete composite segment is used to ensure bearing capacity and closure precision. Thickened edge u-shaped rib and ultra-high toughness concrete pavings are employed together to improve the durability of the orthotropic deck. A single-pile and single-column foundation is fully employed, while the maximum diameter of the steel composite pile is 5 m. It is found that the construction time is reduced by 40%, the wave flow force is decreased by 80%, the scouring depth is decreased by 20% and the cost is reduced by 30% compared with group pilings. In addition, this avoids durability problems of the pile cap due to group pilings. The use of a prefabricated exterior shell with onsite cast concrete for the interior pier-top blocks of the 50-m non-navigation span solves the problems associated with the bearing force, durability, construction availability and quality control of the pier-top block.